Bone marrow failure, somatic rescue by p53 inactivation, and enhanced leukemogenesis in germ line ERCC6L2 disease - Schimmer, Roman R.; Klemm, Nancy; Fullin, Jonas; Topçu, Ebru; Treacy, Milena; Zielińska, Karolina A.; Doerdelmann, Cyril; Devesa-Serrano, Daphne; Lock, Melissa; Caiado, Francisco; Koch, Christian; Dietliker, Nadja; et al. (Elsevier, 2026)
Recessively inherited loss-of-function mutations in excision repair cross-complementing 6–like 2 (ERCC6L2) cause a bone marrow failure (BMF) syndrome characterized by moderate cytopenias, frequent somatic TP53 mutations, and a propensity to develop myeloid malignancies. The pathophysiology and molecular mechanisms underlying the BMF syndrome as well as its association with TP53-mutant clonal hematopoiesis and myeloid malignancies have remained poorly understood. Using novel preclinical in vitro and in vivo model systems, we demonstrate that Ercc6l2 maintains the competitive fitness of hematopoietic stem and progenitor cells (HSPCs) by mitigating replication stress. Sustained replication stress and DNA damage in Ercc6l2-deficient HSPCs cause p53 pathway activation followed by cell cycle arrest and apoptosis. Moreover, Ercc6l2 deficiency results in decreased expression of master hematopoietic regulators Runx1 and Gata1 in HSPCs. Altogether, loss of Ercc6l2 leads to reduced HSPC numbers, bone marrow hypocellularity, and cytopenias. Notably, somatic Trp53 mutations restore cellular fitness of Ercc6l2-deficient HSPCs by abrogating p53 pathway activation and restoring Runx1 and Gata1 expression, thereby correcting the BMF phenotype. However, p53 loss fails to normalize replication stress, allowing for the accumulation of DNA damage over time, which increases the likelihood for leukemic transformation. Our data uncover the pathogenesis of ERCC6L2 disease and provide a prototypic example of clonal compensation in BMF syndromes, in which somatic mutations in leukemia-associated genes, in this case TP53, transiently improve blood cell production at, however, the expense of increasing leukemogenic potential.